MARKETING STRATEGY OF MUHAMMADIYAH SELOGIRI HOSPITAL IN 2025: DESCRIPTIVE QUALITATIVE - Hartanto, Bagus Dwi; Noor, Hesty Latifa; Susanto, Anton; Pereira, Rita Ximenes; Araujo, Bendita Ramos da Costa (LPPM Universitas Duta Bangsa Surakarta, 2025)
Marketing strategy is a crucial component in hospital management,playing a significant role in enhancing competitiveness and expanding public outreach. In the context of healthcare services, hospitals are not only required to provide high-quality services but also to effectively introduce those services through marketing strategies tailored to community needs. This study aims to describe the marketing strategies implemented at Muhammadiyah Selogiri Hospital in 2025 using the 4P marketing mix approach: Product, Price, Place, and Promotion. This research employed a descriptive method with a qualitative case study approach. Data were collected through in-depth interviews with key and supporting informants, direct field observation, and document analysis. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing. The research findings indicate that the product strategy of Muhammadiyah Selogiri Hospital focuses on services aligned with the needs of the community, such as 24-hour emergency care, specialist polyclinics, inpatient care, medical check-ups, and home visit services. The pricing strategy is determined through unit cost analysis, adjusted to the local economic conditions, with evaluations conducted every three months. The place strategy involves direct engagement with the community, health centers, and local leaders to expand service coverage. Meanwhile, the promotion strategy combines digital media like social media with conventional methods such as banners and brochures. The study concludes that Muhammadiyah Selogiri Hospital has implemented a comprehensive and adaptive marketing strategy. The successful implementation of this strategy is influenced by cross-unit collaboration, structured planning, and regular evaluations. This approach helps the hospital maintain its relevance and presence amidst the changing needs and expectations of the public regarding healthcare services.